Trends and Patterns of Systemic Glucocorticoid Prescription in Primary Care Institutions in Southwest China, from 2018 to 2021 - Li X; Zeng Z; Fan X; Wang W; Luo X; Yang J; Chang Y (Dove Medical Press, 2023)
Xiaoyi Li,1,* Zhen Zeng,2,* Xingying Fan,1,3 Wenju Wang,4 Xiaobo Luo,4 Junli Yang,1 Yue Chang1,3,* 1School of Medicine and Health Management, Guizhou Medical University, Guiyang, Guizhou Province, People's Republic of China; 2Second Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, Guiyang, Guizhou Province, People's Republic of China; 3Center of Medicine Economics and Management Research, Guizhou Medical University, Guiyang, Guizhou Province, People's Republic of China; 4School of Public Health, Guizhou Medical University, Guiyang, Guizhou Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Yue Chang; Xingying Fan, School of Medicine and Health Management, Guizhou Medical University, Gui'an New District, Guiyang, Guizhou Province, People's Republic of China, Email 4567401@qq.com; 741284752@qq.comPurpose: The purpose of this study was to investigate the prescribing patterns and usage trends of systemic glucocorticoids in primary care institutions located in Southwest China from 2018 to 2021.Materials and Methods: A retrospective cross-sectional analysis of systemic glucocorticoids prescriptions was conducted in 32 primary care institutions located in Southwest China between 2018 and 2021. Prescriptions of systemic glucocorticoids were classified as appropriate or inappropriate use. Inappropriate use was further classified into (1) inappropriate indications and (2) inappropriate selection of glucocorticoids. Generalized estimation equations were employed to investigate the factors associated with inappropriate utilization of systemic glucocorticoids. The seasonal autoregressive integrated moving average (SARIMA) model was employed to predict the rate of inappropriate glucocorticoids prescriptions.Results: A total of 203,846 (92.89%) prescriptions were included, both the number of systemic glucocorticoids prescriptions and inappropriate prescriptions increased in winter. Diseases of the respiratory system (68.90%) were the most frequent targets of systemic glucocorticoids use. Of all prescriptions, 73.18% exhibited inappropriate indications, while 0.05% demonstrated inappropriate selection. The utilization of systemic glucocorticoids was deemed inappropriate for diseases of the respiratory system (94.19%), followed by diseases of the digestive system (87.75%). Physicians, who were female or younger than 33 years old, possess lower levels of education and professional titles and exhibit a higher likelihood of inappropriately prescribing systemic glucocorticoids. The phenomenon of inappropriate glucocorticoids use was commoner among male patients aged 65 years and older. After conducting model verification, it was determined that the SARIMA model could be used to predict the monthly rate of inappropriate systemic glucocorticoids prescriptions in primary care institutions in southwest China.Conclusion: The inappropriate use of systemic glucocorticoids remains a significant concern in primary care institutions. In this regard, continuing education and professional knowledge training of physicians should be strengthened in the future.Keywords: systemic glucocorticoids, primary care institutions, prescription patterns, inappropriate use, usage trends